Degradation of Zearalenone by Essential Oils under In vitro Conditions - Perczak, Adam; Juś, Krzysztof; Marchwińska, Katarzyna; Gwiazdowska, Daniela; Waśkiewicz, Agnieszka; Goliński, Piotr (Frontiers in Microbiology, 2016)
Essential oils are volatile compounds, extracted from plants, which have a strong odour. These compounds are known for their antibacterial and antifungal properties. However, data concerning degradation of mycotoxins by these metabolites are very limited. The aim of the present study was to investigate the effect of essential oils (cedarwood, cinnamon leaf, cinnamon bark, white grapefruit, pink grapefruit, lemon, eucalyptus, palmarosa, mint, thymic and rosemary) on zearalenone reduction under various in vitro conditions, including the influence of temperature, pH, incubation time and mycotoxin and essential oil concentrations. The degree of zearalenone reduction was determined by HPLC method. It was found that the kind of essential oil influences the effectiveness of toxin level reduction, the highest being observed for lemon, grapefruit, eucalyptus and palmarosa oils, while lavender, thymic and rosemary oils did not degrade the toxin. In addition, the decrease in zearalenone content was temperature, pH as well as toxin and essential oil concentration dependent. Generally, higher reduction was observed at higher temperature in a wide range of pH, with clear evidence that the degradation rate increased gradually with time. In some combinations (e.g. palmarosa oil at pH 6 and 4 or 20C) a toxin degradation rate higher than 99% was observed. It was concluded that some of the tested essential oils may be effective in detoxification of zearalenone. We suggested that essential oils should be recognized as an interesting and effective means of zearalenone decontamination and/or detoxification.